The impact of digital literacy on farmers' pro-environmental behavior: an analysis with the Theory of Planned Behavior - Lu, Shen; Sun, Zenan; Huang, Man (Frontiers in Sustainable Food Systems, 2024)
Introduction The rapid development of agriculture has brought about significant negative impacts on the environment, such as land pollution and ecological degradation. The root cause of environmental issues lies in human behavior, with improper farming practices by farmers being a major contributor to agricultural pollution. This paper explores the relationship between farmers' digital literacy and their pro-environmental behaviors, examining the mediating roles of subjective norms, behavioral attitudes, and perceived behavioral control. Additionally, it investigates the varying impacts of digital literacy on PEB among farmers with different levels of education, social capital, and household income. Methods Based on data from the China Land Economic Survey (CLES), this study utilizes an ordered probit regression analysis method to analyze data from 923 sample respondents in 24 villages in Jiangsu Province. All analyses were conducted using Stata 15.0. Results The research findings indicate that digital literacy enhances the likelihood of farmers engaging in PEB. This practice is achieved by reinforcing farmers' subjective norms, strengthening their behavioral attitudes, and enhancing their perceived behavioral control (as the core elements in the Theory of Planned Behavior theory), thereby promoting the implementation of PEB among farmers. Further analysis reveals that digital literacy plays a crucial role in enhancing PEB among farmers with higher levels of education, social capital, and household income. Discussion The results of this study suggest that policymakers should enhance farmers' digital literacy and implement specific measures to improve farmers' subjective norms, behavioral attitudes, and perceived behavioral control. When the digital literacy and willingness for PEB are improved, farmers may engage in environmentally friendly practices.